Exploring Teacher’s Beliefs and Practices in Teaching Speaking Skill for Junior High School Students: A Case Study - Adinda Maharani; Hilmansyah Saefullah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This qualitative case study investigates an English teacher’s beliefs and instructional practices in teaching speaking skills at a junior high school in Karawang, Indonesia. The research focuses on understanding the teacher’s beliefs on speaking instruction and how these beliefs are implemented in the classroom. Data were gathered through semi-structured interviews, classroom observations, and analysis of relevant documents. The results indicate that the teacher holds thoughtful and consistent beliefs about the value of speaking as a tool for communication and self-expression. He adopts a flexible teaching role, functioning as a teacher, friend, and supporter based on students’ needs. To foster student engagement and confidence, he utilized the Grammar Translation Method (GTM) alongside interactive games. While many of his practices were consistent with his stated beliefs, some discrepancies arose due to contextual limitations such as time constraints and lesson content. This study emphasizes the significance of aligning teachers’ beliefs with their classroom practices to enhance the effectiveness of speaking instruction in EFL settings.